PENGARUH SUHU PERMUKAAN LAUT TERHADAP HASIL TANGKAPAN IKAN CAKALANG YANG DIDARATKAN DI PELABUHAN PERIKANAN NUSANTARA (PPN) SIBOLGA SUMATERA UTARA - Ananda Yuli Fazilah Tanjung; Mardame Pangihtan Sinaga; Ewin Handoco S (Journal of Research and Publication Innovation, 2025)
Skipjack tuna is a fish that has very high economic value and skipjack tuna catch is export scale which is exported to various countries, such as Japan, Thailand, and England. Skipjack tuna is the main community catch around Aceh and Sumatra's western waters, so people depend on Skipjack tuna catch in large quantities. Sea Surface Temperature (SST), as measured by satellites, is the condition of the sea surface layer because infrared radiation is absorbed and reflected by surface water molecules. The thickness of the water surface whose temperature is measured depends on the wavelength of the radiation. For wavelengths between 3-14 μm, the thickness is less than 0,1 mm, because what is measured is the water surface temperature, its use in oceanography depends on the ability to interpret it, namely to determine the temperature in the surface layer up to several meters down, which according to experts call Sea Surface Temperature (SST). The reason for the high correlation between SST and skipjack tuna number caught in the west-east season is thought to be because the skipjack tuna distribution in the water area is not only influenced by one particular oceanographic factor. The low correlation between SST and skipjack tuna number caught in the second transition season is thought to be due to the optimum temperature in that season for skipjack tuna body, where the results from satellite imagery of the first transition season have SPL of 28,3-29,4 ºC. The highest catch of skipjack tuna occurred in December 2023 with a total of 2.023.543 kg, and the lowest was in June 2023 with a value of 12,678 kg. In the linear regression analysis, the relationship between SST and skipjack tuna catches in transition season II received a significance (F) value of 0,05, where sea surface temperature affected skipjack tuna catches.